Impact of Incremental Zinc Sulphate Monohydrate on Productive Performance, Blood Chemistry and Egg Quality Dynamics of Bovan Black Strain - Osayande, Unity Daniel; Iwenekha, Matthew; Jimoh, Olatunji Abubakar; Akangbe, Esther Eghosa; Unukevwere, Jerome Unuavwogbikuomawho; Obajuluwa, Olusola Victor (The Indian Journal of Animal Sciences, 2026)
This study evaluated the effect of zinc sulphate monohydrate on performance characteristics and blood chemistry of laying birds. A total of 100 Point of Lay (PoL) Bovan Black hens were randomly assigned to four dietary treatments: control (T1, 0mg/kg zinc), and treatments T2 (30mg/kg), T3 (60mg/MT), and T4 (90mg/kg). Birds were allowed access to feed and water ad libitum for 12 weeks. Parameters assessed included:  feed proximate composition (%), Hen-Day Production (HDP), feed intake, egg weight, feed efficiency, percentage mortality, and blood biochemical indices. Dry matter ranged from 85.07% (T1) to 82.39% (T4), as crude protein slightly increased from 16.68.58% (T1) to 16.94% (T4). While zinc levels peaked in T4 (22.59 mg/kg), calcium (1.17%) and phosphorus (0.64–0.65%) remained constant across treatments. HDP was significantly (p